Immediate bracket: A new horizon (International Journal of Biomedical Research, 2016)
Brackets are the key for success in the correction of teeth. Often we see that breakage and loss of the bracket hampers the treatment and can cause mayhem. Replacing is always expensive and a hefty toll is placed on the patient. Our method is an arrangement this expensive replacement.